Tres conceptos de escasez - Iguíñiz Echeverría, Javier (2010)
We suggest the need to distinguish between three types of scarcity: absolute, relative and comparative. In this way we relate scarcity to the three main components of the economy: production, exchange and distribution. During the XX century, scarcity has been, by far, mainly used to deal with the second.